PERAN OTORITAS JASA KEUANGAN DALAM PERMOHONAN KEPAILITAN PERUSAHAAN ASURANSI (ANALISIS PUTUSANNOMOR 1016 K/PDT.SUS-PAILIT/2016) - Sari Rezeki Indra; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (Universitas Sumatera Utara, 2018)
Abstract Article 50 of Law No. 40 of 2014 on R.I No. 40 of 2014 concerning insurance, a request for bankruptcy statement against an insurance company, an Islamic insurance company, a reinsurance company or an Islamic reinsurance company pursuant to a law submitted by the Financial Services Authority. The problem is the regulation of the role of the Financial Services Authority in the insurance bankruptcy application, the role of the Financial Services Authority in the insurance bankruptcy application and the legal consequences arising if the insurer is declared bankrupt (Case Study Decision Number 1016 K/Pdt.Sus-Bankrupt /2016). The method is normative legal research. The data source is secondary data. An important data analysis in a framework study provides an answer to the problem studied. The conclusion is a request for bankruptcy statement against insurance companies, sharia insurance companies, reinsurance companies or sharia reinsurance companies only submitted by the Financial Services Authority. The centralized system of regulation and supervision of financial services and financing including the filing of bankruptcy statements of financial services and financing institutions including insurance companies essentially aims to ensure the interests of all parties in order to create a stable economic system through the financial services sector and insurance company financing. Legal consequences arise if the insurance company declared bankruptcy resulted in the entire property of the debtor bankrupt in the public confiscation so that the debtor bankruptcy loses his right in civilian control and take care of his wealth including bankruptcy property, since the date of decision of bankruptcy statement is pronounced. Keywords: Bankruptcy, Insurance Company, Authority Of Financial Services.